Internal affairs - Alonzo, John A. 1934-2001; Bean, Henry ca. 20. Jh; Gere, Richard 1949-; Garcia, Andy 1956-; Travis, Nancy 1961-; Metcalf, Laurie 1955-; Wood, Elijah 1981- (Paramount Pictures, 2001)
Dennis Peck knows how to get around the law, because he is a cop. Raymond Avilla is the investigator who is determined to bring Peck to justice, even as Peck threatens Avilla's career, marriage, and sanity
Original: USA, Kanada 1990
Keywords: Los Angeles (Calif.) / Police Department / Internal Affairs Division / Drama; Feature films; Police / Complaints against / Drama; Police corruption / United States / Drama; Los Angeles (Calif.) / Police Department / Internal Affairs Division; Police / Complaints against; Police corruption; United States; Drama; Film; DVD-Video